Design and Development Process for a novel Technology Capable of Providing a New Breaking Force Attenuating Sports Surface. (2016) - Walker, Alexander
Abstract: Lower limb loading rate is a major contributor to athletic injury because it represents the stress being absorbed by an athlete's lower limbs that makes them vulnerable to stress fractures, as well as knee and ankle joint injuries. This research therefore sought to identify a means by which lower limb loading rates could be reduced and therefore the risk of overloading injury reduced. A sports surface that encourages elastic deformation during contact in both the horizontal anterior-posterior direction and the horizontal medial-lateral direction through a process of horizontal deformation and displacement may result in reduced foot and limb loading. This surface should maximise horizontal energy attenuation in order to reduce the risk of injury while at the same time provide satisfactory energy return to avoid player fatigue. Effective product research and development methods centre on the ways in which the activities can be effectively planned, controlled and implemented. The process can be regarded as a sequence of activities and decisions which progress a problem solving process from the initial identification of the problem, through to a final implementable design solution. The process of design is fundamentally an iterative method, which comprises the articulation of the problem which is to be solved, collecting and codifying pertinent information, the divergent exploration of potential problem solutions, convergence towards a favourable solution, and finally, the detailed implementation and optimisation of the design solution. The creative process followed, has resulted in the design of a novel, and commercially improved modular plastic tile sports surface system. This has been realised through the development of an innovative, sustainable, shock attenuating tile and connector geometry, which aims to reduce braking forces on the sports surface to acceptable levels, and thus reduce the risk of athlete injury. This research is significant as currently no sports surface exists which specifically targets horizontal force reduction, as a means to reduce injury rates.